(untitled) (Medico Legal Update, 2021)
Information-seeking patterns of vaccine receivers have over time been determined their vaccine decisions. These patterns are mostly represented by their demographic representation. Therefore it is interesting to review how these demographic representations have affected vaccine choices in the past. This paper would serve as a guide to health officials, human communication experts and pharmaceutical companies in the development and distribution of Coronavirus vaccines when it is ready